DEVELOPMENT OF GAME-BASED LEARNING MODELS AS AN EFFORT TO INCREASE STUDENTS’ LEARNING MOTIVATION IN ENTREPRENEURSHIP LEARNING SUBJECTS FOR CLASS XI STUDENTS OF SMK NEGERI 1 BANGKO - Suraini; Sumarno; Kartikowati, Sri (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
This paper is development research that aims to determine the process, feasibility, and students’ response to game-based learning models as an effort to increase learning motivation in entrepreneurship learning subjects for class XI students of SMK Negeri 1 Bangko. The instruments used in the research were validation sheets and questionnaires, and the data that had been collected were analyzed. Data analysis used descriptive statistical analysis obtained from data collection of material expert validation and model experts sheets, while data collected from questionnaires were used to analyze as an effort to increase students’ learning motivation. The results of the research in the first stage were validated by material experts at 3.00 with a good category of content aspects and at 3.66 with a very good category of several revisions and not feasible testing presentation. In the second stage of material expert validation, the content aspect was 3.5 with a very good category and presenting several suggestions and feasible testing aspects was 3.83 with a very good category. In the first stage of validation by model experts, there were 2.8 with a good category of several revisions and not feasible testing, In stage II, the validation average by model experts was 3.3 with a very good category and feasible testing. Based on the results of the game-based learning model development, the result indicates that it was feasible to be tested in order to find out how students respond to game-based learning models as an effort to increase student learning motivation, which involved 32 students of class XI at SMK Negeri 1 Bangko as research subjects. An assessment score of 2.54 indicates that aspects of students' learning motivation before applying the game-based learning model are in a high category. The assessment score of 3.02 indicates that the aspect of students’ learning motivation after applying the game-based learning model is in the very high category.